2016
DOI: 10.1080/17453674.2016.1256940
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of fixation stiffness from flexible to stiff in a rat model of bone healing

Abstract: Background and purposeConstant fixator stiffness for the duration of healing may not provide suitable mechanical conditions for all stages of bone repair. We therefore investigated the influence of stiffening fixation on callus stiffness and morphology in a rat diaphyseal osteotomy model to determine whether healing time was shortened and callus stiffness increased through modulation of fixation from flexible to stiff.Material and methodsAn external unilateral fixator was applied to the osteotomized femur and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 26 publications
1
44
0
2
Order By: Relevance
“…In this study we showed that when reverse dynamization, from flexible to rigid fixation, was applied at 3 weeks the healing outcome at the end of the treatment period was the same as the dynamization regimen (Claes et al, 2011; Bartnikowski et al, 2016). However, when reverse dynamization was applied at 1 week the healing outcome was exceedingly superior to that of the dynamized group (Table 1), constant rigid and flexible fixation groups (Bartnikowski et al, 2016). On the contrary, the dynamization regimen at 1 week was detrimental to bone healing when compared to any of the other groups tested (Claes et al, 2009).…”
Section: Reverse Dynamizationmentioning
confidence: 58%
See 2 more Smart Citations
“…In this study we showed that when reverse dynamization, from flexible to rigid fixation, was applied at 3 weeks the healing outcome at the end of the treatment period was the same as the dynamization regimen (Claes et al, 2011; Bartnikowski et al, 2016). However, when reverse dynamization was applied at 1 week the healing outcome was exceedingly superior to that of the dynamized group (Table 1), constant rigid and flexible fixation groups (Bartnikowski et al, 2016). On the contrary, the dynamization regimen at 1 week was detrimental to bone healing when compared to any of the other groups tested (Claes et al, 2009).…”
Section: Reverse Dynamizationmentioning
confidence: 58%
“…For dynamization implemented at the later stages of healing, accelerated bone healing is more likely a consequence of bone adaptation following Wolff's law rather than fixator dynamization itself. In fact, this hypothesis was confirmed using the reverse dynamization regimen in the same 1 mm osteotomy rat model as was used by Claes' group (Bartnikowski et al, 2016). In this study we showed that when reverse dynamization, from flexible to rigid fixation, was applied at 3 weeks the healing outcome at the end of the treatment period was the same as the dynamization regimen (Claes et al, 2011; Bartnikowski et al, 2016).…”
Section: Reverse Dynamizationmentioning
confidence: 64%
See 1 more Smart Citation
“…By 3 weeks the effect of reverse dynamization was lost and the outcome was equivalent to that occurring under standard, forward dynamization (Fig. ) . The modest gains produced by forward dynamization are not surprising considering our study demonstrating that any improvement noted when forward dynamization was implemented at the later stages of healing, was more likely a consequence of bone adaptation following Wolff's law, rather than fixator dynamization as such (Fig.…”
Section: Chondrogenesis and Cartilage Repairmentioning
confidence: 60%
“…To study this we created 1 mm, mid‐diaphyseal osteotomies in the rat femur. All defects were fixed initially at low axial stiffness, and reverse dynamization (increased stiffness) applied at various times from 3 days to 3 weeks . The optimum time for increasing the stiffness of fixation occurred 7 days after surgery (Fig.…”
Section: Chondrogenesis and Cartilage Repairmentioning
confidence: 99%